Case report: lymphohistiocytic myocarditis with severe cardiogenic shock requiring mechanical cardiocirculatory support in multisystem inflammatory syndrome following SARS-CoV-2 infection - Bemtgen, Xavier; Klingel, Karin; Hufnagel, Markus; Janda, Ales̆; Bode, Christoph; Staudacher, Dawid; Supady, Alexander; Jandová, Ilona (Frontiers in Cardiovascular Medicine, 2021)
Multisystem Inflammatory Syndrome (MIS) is a novel hyperinflammatory syndrome associated with SARS-CoV-2 infection. It predominantly affects children (MIS-C) a few weeks after a usually asymptomatic SARS-CoV-2 infection and is only rarely seen in adults above 21 years (MIS-A). Only scarce data on histological findings in both pediatric and adult patients has been published so far. An 18-year-old male patient was admitted to hospital in a febrile state, which progressed to severe cardiogenic shock and multi-organ failure requiring extracorporeal life support. Myocardial biopsy revealed small vessel-associated immune cell infiltrates. Diagnosis of MIS-C was made after ruling out all potential differential diagnosis. Use of immunosuppressive treatment with steroids, interleukin-1 blockade and high-dose intravenous immunoglobulins resulted in the patient's full recovery. Multisystem Inflammatory Syndrome (MIS) is a new differential diagnosis of cardiac dysfunction in pediatric and adult patients. The lack of myocardial necrosis differentiates the disease from other viral myocarditis and offers an explanation for the fast response to immunomodulatory therapy and the favorable prognosis. The preceding SARS-CoV-2 infection might only have been mildly symptomatic or even asymptomatic.
Gesehen am 05.11.2021